Implementation of the ADLX Introflex Integrated Curriculum in the Formation of Religious Character in Elementary Schools - Suparti, Sri; Widyasari, Choiriyah (Universitas Muhammadiyah Surakarta, 2025)
The development of religious character in primary school pupils constitutes a fundamental pillar of integrated Islamic education. This study aimed to empirically examine the implementation of the ADLX Introflex Integrated Curriculum in cultivating religious character among pupils at IQRO' Nogosari Integrated Islamic Primary School. Adopting a qualitative approach with a phenomenological design, the research involved key stakeholders—including the school principal, teachers, and pupils—as participants. Data were collected via in-depth interviews, participant observation, and document analysis. The data were analysed using the interactive model proposed by Miles and Huberman. The findings reveal that the implementation of the ADLX Integrated Curriculum is organised around core elements: Active Learning, Deep Learning, Learner Experience, and the INTROFLEX approach. The curriculum is delivered through curricular, co-curricular, and extracurricular channels. The formation of religious character is specifically supported by programmes such as Iqro’ Inspire, Tahsin and Tahfidz Al Bayan, Worship Monitoring, and Islamic Personal Development (BPI). The study also underscores the ongoing collaboration among teachers, school administration, and parents in fostering pupils’ religious character. The ADLX Introflex curriculum holds substantial implications for elevating pupils’ spiritual awareness and enriches the wider discourse on character education within the context of Islamic tarbiyah.